2012
DOI: 10.1371/journal.pone.0047509
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Implants Do Not Aggravate the Tissue Reaction in Rat Brain

Abstract: Chronically implanted microelectrodes are an invaluable tool for neuroscientific research, allowing long term recordings in awake and behaving animals. It is known that all such electrodes will evoke a tissue reaction affected by its’ size, shape, surface structure, fixation mode and implantation method. However, the possible correlation between tissue reactions and the number of implanted electrodes is not clear. We implanted multiple wire bundles into the brain of rats and studied the correlation between the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 41 publications
3
16
0
Order By: Relevance
“…The general tissue reactions to the high-density (HD) probes were qualitatively fully comparable to the tissue reactions observed in our previous studies, as well as to those reported by other laboratories1416192021. In brief, we found a dense astrocytic scar of about 10–20 μm encapsulating the probes diminishing further away from the wound, and a relatively sparse distribution of microglia confined to the immediate vicinity of the probes (Fig.…”
Section: Resultssupporting
confidence: 89%
See 3 more Smart Citations
“…The general tissue reactions to the high-density (HD) probes were qualitatively fully comparable to the tissue reactions observed in our previous studies, as well as to those reported by other laboratories1416192021. In brief, we found a dense astrocytic scar of about 10–20 μm encapsulating the probes diminishing further away from the wound, and a relatively sparse distribution of microglia confined to the immediate vicinity of the probes (Fig.…”
Section: Resultssupporting
confidence: 89%
“…In fact, several areas surrounding the LD probes (but none surrounding the HD probes) did not have any reactive astrocytes (Fig. 2j), which was never observed in our previous experiments161920. Hence, given that the probes used here are very similar apart from with respect to density, we propose that the mechanical forces between probes and neural tissues that arise because of differences in inertial forces every time the animal accelerates or because of difference in gravitational pull on the implants trigger astrocyte reactivity and the development of a glial scar.…”
Section: Discussionsupporting
confidence: 67%
See 2 more Smart Citations
“…3F). Along with reducing penetration damage proportional to diameter, two separate penetrations cause less damage than a single penetration with coupled devices, particularly with 1-mm separation (50,51) and our illuminator's increased mechanical compliance vs. glass (52). We illustrate light spread of at least 1 mm laterally along the illuminator tip with multicontact electrode recordings from representative neurons (Fig.…”
Section: Significancementioning
confidence: 94%